Overcoming rural underdevelopment : proceedings of a Workshop on Alternative Agrarian Systems and Rural Development, Arusha, Tanzania, 4-14 April, 1979 - Ghai, Dharam P.; University of Dar es Salaam; International Labour Office (Geneva : International Labour Off., 1979)
This book is based on the presentations and discussions that took place at a workshop on 'Alternative Agrarian Systems and Rural Development' organized jointly by the University of Dar es Salaam and the International Labour Office. The book contains discussion of innovative attempts in organization of agricultural production in twelve countries classified under three categories: peasant agriculture, communal farming, and system of cultivation in transition from private to cooperative production
Sponsored by the University of Dar es Salaam and the International Labour Office.
osc 29/01/2019
Loans
Keywords: Rural development; Villages; Land tenure; Agriculture and state